LEARNING PROGRAM EVALUATION AND TEACHING QUALITY IMPROVEMENT: A QUANTITATIVE CIPP STUDY - Desembra Sohilait; Clara Samarama; Sarni Reniwurwarin; Nur Yanti Habu; Iwan Yusuf (EDUCATIONE, 2026)
This study was motivated by the absence of a comprehensive and systematic evaluation of school learning programs designed to improve teaching quality at SMP Negeri 3 Ambon. Although the school has implemented several improvement initiatives, including teacher training, academic supervision, project-based curriculum development, and the strengthening of digital learning facilities, their overall effectiveness had not been quantitatively assessed. Therefore, this study aimed to evaluate the effectiveness of these learning programs using the Context, Input, Process, and Product (CIPP) model. A descriptive quantitative design was employed involving 20 respondents, consisting of teachers and educational staff, selected through total sampling. Data were collected using a Likert-scale questionnaire developed according to the four CIPP dimensions and analyzed through descriptive statistics and Pearson correlation using SPSS version 25. The findings revealed that the overall implementation of the learning programs was rated very good, with a mean score of 4.41. Among the CIPP dimensions, product received the highest score (4.70), followed by context (4.60), process (4.40), and input (4.30). In addition, the Pearson correlation coefficient of 0.781 (p < 0.05) indicated a significant relationship between learning program implementation and teaching quality improvement. The study concludes that the CIPP model is effective for comprehensively evaluating school learning programs and for identifying strengths and areas for improvement. These findings provide empirical support for school leaders and policymakers in making evidence-based decisions to enhance teaching quality. Future research is recommended to involve larger samples, multiple schools, and mixed-method approaches to produce broader and deeper evaluation results.